STUDENTS' PERCEPTIONS OF THE ROLE OF SONGS IN ENHANCING ENGLISH VOCABULARY MASTERY - Mewi Dinda Arcila Waruwu; Noniat Zega; Priskila Destalenta Tafona'o; Dodi Kardo Wijaya Waruwu; Berkris Yopitama Lase (LPPM Universitas PGRI Jombang, 2025)
Vocabulary mastery is a fundamental aspect of English language learning, contributing significantly to students' communication skills. This study aims to explore students' perceptions of the role of songs in enhancing English vocabulary mastery. Using a qualitative approach, data were collected through a questionnaire consisting of 15 Likert-scale statements, distributed to eighth-grade students at SMP Negeri 3 Lolofitu Moi. The results indicate that most students perceive songs as an effective tool for improving vocabulary retention, motivation, and pronunciation. The engaging nature of songs makes learning more enjoyable, leading to increased interest and independent learning outside the classroom. However, some students reported that while songs help with memorization, they still struggle with applying new vocabulary in conversations. These findings suggest that songs can be a valuable supplementary learning resource, but should be combined with other interactive teaching methods for maximum effectiveness. This study provides insights for educators to design more engaging vocabulary learning strategies.